Propuesta de un modelo de gestión sostenible para el sistema de riego Maconta Abajo en la provincia de Manabí - Galarza Álava, Yaser Francoise (2024)
The objective of this research was to propose a management model that contributes to the sustainability of the "Maconta Abajo" technified irrigation system in Colón parish, Portoviejo. The methodology was divided into two phases. In the first phase, a descriptive, bibliographic, and explanatory approach was employed to characterize the socio-productive situation of the users. Additionally, a land use analysis was conducted using the Soil-Adjusted Vegetation Index (SAVI) to evaluate the impact before and after the irrigation system's implementation. The second phase involved an exploratory, propositional, and bibliographic approach, focusing on developing a sustainable management model for the irrigation system. This proposal comprehensively addressed administrative aspects, including identifying the roles and responsibilities of the irrigation board. The technical- operational component was based on an irrigation schedule using parameters such as reference evapotranspiration (ETo), crop coefficient (Kc) adjusted to local climatic conditions, crop evapotranspiration (ETc), as well as the net and total irrigation needs and the creation of a pumping schedule. The productive component involved determining the number of hectares under irrigation and their production, while the economic component consisted of creating a tariff plan and defining the legal framework of water users' rights and obligations. This proposal aims to optimize the efficiency and productivity of the Maconta Abajo irrigation system.